Adapted physical therapy exercises for students with cerebral palsy - Reyes, Mitsi Agnes T. (2006)
The study presented the development and validation of an adapted PE program consisting of physical therapy exercises for students with cerebral palsy. The APTEPC was implemented at Paranaque Elementary School and Sto. Nino Elementary School for three months, with a total of 25 sessions. The results showed that there is a significant agreement among raters' ratings of the respondetns' performance on the pretest and posttest. This shows that the program was effective in all areas. It was recommended that further testing be done to strengthen validity and reliability of the program, the program be done at least twice weekly on a regular basis, teachers implementing the program be trained first by physical therapists with SPED background, and a training manual be developed.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Cerebral palsied children -- Philippines -- Paranaque City; Cerebral palsy -- Exercise therapy -- Philippines -- Paranaque City; Physical therapy for children -- Philippines -- Paranaque City